Journal Analysis Study of Students' Independent Character Implementation in Online Learning During the Covid-19 Pandemic: Study Analisis Jurnal Implementasi Karakter Mandiri Siswa dalam Pembelajaran Daring di Masa Pandemi Covid-19 - Tri Indah Yanti; Muhlasin Amrullah (Universitas Muhammadiyah Sidoarjo, 2022)
This study examines the implementation of students' independent character in online learning during the COVID-19 pandemic. The research focuses on students, teachers, and parents as subjects, employing the Mustika zed model for data analysis. Through a comprehensive literature review using Google Scholar, the study explores the effects of online learning on students' habits and the need for parental assistance in completing tasks. The research reveals that the implementation of independent character can benefit students across different grade levels, with habituation materials playing a crucial role. The study concludes by highlighting the importance of incorporating independent character development in learning planning. This research contributes to understanding the impact of online learning and provides implications for fostering students' independence in education. Highlights: Online learning during the COVID-19 pandemic has led to a decline in students' learning independence. The implementation of habituation materials in online learning can effectively address the loss of good habits developed in traditional school settings. This research emphasizes the importance of fostering students' independent character through online learning and highlights the role of parents, teachers, and students in adapting to the challenges posed by the pandemic. Keywords: Online learning, students, learning independence, COVID-19 pandemic, habituation materials.